2014
DOI: 10.1016/j.freeradbiomed.2013.10.806
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase-1 modulates Nrf2-dependent transcription

Abstract: The basic leucine zipper (bZIP) transcription factor Nrf2 has emerged as a master regulator of intracellular redox homeostasis by controlling the expression of a battery of redox balancing antioxidants and phase II detoxification enzymes. Under oxidative stress conditions, Nrf2 is induced at the protein level through redox-sensitive modifications on critical cysteine residues in Keap1, a component of an E3 ubiquitin ligase complex that targets Nrf2 for proteasomal degradation. Poly(ADP-ribose) polymerase-1 (PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 45 publications
2
46
1
Order By: Relevance
“…Biotin-DNA pull-down was performed as reported previously [60]. In brief, cells were lysed in RIPA buffer containing 1 mM DTT, 1 mM phenylmethylsulfonyl fluoride (PMSF), and 1% protease inhibitor cocktail (Sigma-Aldrich).…”
Section: Biotin-dna Pull-downmentioning
confidence: 99%
“…Biotin-DNA pull-down was performed as reported previously [60]. In brief, cells were lysed in RIPA buffer containing 1 mM DTT, 1 mM phenylmethylsulfonyl fluoride (PMSF), and 1% protease inhibitor cocktail (Sigma-Aldrich).…”
Section: Biotin-dna Pull-downmentioning
confidence: 99%
“…Furthermore, PARP-1 was also shown to act as a transcriptional coactivator for NRF-2. PARP-1 binds NRF2 indirectly through the adaptor protein Maf and upregulates the its transcriptional activity [58]. It is important to note that the interactions between PARP-1 and NRF-1/2 are independent of the enzymatic activation of PARP-1, which can be crucial in cells recovering from sublethal oxidative injury (Box 1)…”
Section: Reviewmentioning
confidence: 99%
“…Some of these pathways are independent of PARylation (e.g., NRFs [57,58]), and are hence capable of preserving mitochondrial activity under stress conditions. These feedforward pathways might be important for cells to recover from sublethal PARP-mediated stress situations [42,49,50].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Loss of BRCA1 (or BRCA2) in cancer can be exploited by targeting PARP1, a facilitator of DNA repair [67]. Recently, Wu et al [68] found that PARP1 interacts directly with small Maf proteins, NRF2’s heterodimeric partners, and that this complex augments Nrf2’s ARE-specific DNA binding, thereby enhancing Nrf2-dependent gene transcription. Thus, one may hypothesize that the therapeutic efficacy obtained by molecular targeting of PARP1 in cancer could be due in part to suppression of Nrf2-mediated DNA repair.…”
Section: Nrf2 Promotes Repair Of Damaged Dnamentioning
confidence: 99%